Resolution of the XX Anniversary Congress of Children's Infectious Diseases Doctors of Russia with international participation «Topical issues of infectious pathology and vaccine prevention» - article Editorial (LLC "Diagnostics and Vaccines", 2022)
Moscow, December 16-17, 2021